The crack propagation path under multiple moving contact loads in rolling contact fatigue. (April 2019) - Shahani, A.R.; Davachi, R.; Babaei, M.
Highlights: A new model is presented which considers multiple moving loads to calculate the remaining life of a surface under the rolling contact fatigue. The fracture mechanics problem is formulated based on the singular integral equations method. By increasing the number of the moving loads with the similar speeds, increasing the distance between the two and three concentrated moving loads the surface cracks join together and grow towards the surface, causing pitting be reduced. When two concentrated moving loads move with different speeds the pitting be reduced. Abstract: This paper proposes a model which considers multiple moving loads to calculate the remaining life of a surface under the rolling contact fatigue. This model is based on the linear fracture mechanics for determining the characteristics of cyclic crack growth. The body under the rolling contact is modeled by a half-plane with an edge crack. Rolling contact is simulated by a translational motion of concentrated forces along the half-plane boundary. The fracture mechanics problem is formulated based on the singular integral equations method and these equations are solved at each step of crack growth, resulting in the stress intensity factors at each step. Then, the crack growth is modeled using the mixed mode fracture criterion for finding the crack path during the growth and the Paris equation for determining the amount of fatigue crack propagation. The effect of the number of moving loads with similar and different speeds applied on the edge of the half-plane, the value of coefficient of friction and the distance between the moving loads with the similar speeds on the crack propagation path and the remaining life have been investigated. It is seen that by increasing the number of the moving loads with the similar speeds on the boundary of the half-plane, increasing the distance between the two and three concentrated moving loads and when two concentrated moving loads move with different speeds, the crack propagation angle compared to the initial crack angle increases and the crack is distracting more inside the surface. As a result, the surface cracks join together and grow towards the surface, causing pitting be reduced.